Conformational Study on Various Tripeptides Containing Threonine: A Density Functional Theory Approach - Shrestha, Manoj Kumar; Dawadi, Nabin; Shrestha, Mani Raj; Sedai, Pukar; Adhikari, Sudip; Lamichhane, Hari Prasad (Amrit Research Journal, 2025)
Density functional theory (DFT) calculations were performed using B3LYP/6-31G* and B3LYP/6-311G* basis sets to investigate the conformational stability of eight tripeptides containing threonine. Each peptide was constructed with threonine flanked by varied amino acids at N- and C-termini including alanine (Ala), arginine (Arg), asparagine (Asn), cysteine (Cys), methionine (Met), aspartic acid (Asp), proline (Pro), serine (Ser) and phenylalanine (Phe). Methionine- Threonine-Phenylalanine showed the lowest total energy (−1029601 kcal mol⁻¹ for 6-31G*, −1029809 kcal mol⁻¹ for 6-311G*). Maximum deviations in bond length (0.053 Å) and bond angle (1.8°) were observed for Proline-Threonine-Serine. Significant α-carbon bond angle deviations of 4.4° and 3.4° were found for Methionine-Threonine-Phenylalanine and Lysine-Threonine-Methionine, respectively. Potential energy surface scans of threonine revealed rotational energy barriers of 6.914 kcal mol⁻¹ (−NH2), 12.711 kcal mol⁻¹ (−COOH), and 8.648 kcal mol⁻¹ (−CH(CH3)OH) group. This study highlights how amino acid sequence influences peptide conformation and intramolecular interactions, contributing to a deeper understanding of protein structure and energetics.